Atmospheric impacts of chlorinated very short-lived substances over the recent past – Part 2: Impacts on ozone - Bednarz, Ewa M.; Hossaini, Ryan; Chipperfield, Martyn P. (Atmospheric Chemistry and Physics, 2023)
Depletion of the stratospheric ozone layer remains an ongoing environmental issue, with increasing stratospheric chlorine from very short-lived substances (VSLS) recently emerging as a potential but uncertain threat to its future recovery. Here the impact of chlorinated VSLS (Cl-VSLS) on past ozone is quantified, for the first time, using the UM–UKCA (Unified Model–United Kingdom Chemistry and Aerosol) chemistry-climate model. Model simulations nudged to reanalysis fields show that in the second decade of the 21st century Cl-VSLS reduced total column ozone by, on average, ∼ 2–3 DU (Dobson unit) in the springtime high latitudes and by ∼0.5 DU in the annual mean in the tropics. The largest ozone reductions were simulated in the Arctic in the springs of 2011 and 2020. During the recent cold Arctic winter of 2019/20 Cl-VSLS resulted in local ozone reductions of up to ∼7 % in the lower stratosphere and of ∼7 DU in total column ozone by the end of March. Despite nearly doubling of Cl-VSLS contribution to stratospheric chlorine over the early 21st century, the inclusion of Cl-VSLS in the nudged simulations does not substantially modify the magnitude of the simulated recent ozone trends and, thus, does not help to explain the persistent negative ozone trends that have been observed in the extra-polar lower stratosphere. The free-running simulations, on the other hand, suggest Cl-VSLS-induced amplification of the negative tropical lower-stratospheric ozone trend by ∼20 %, suggesting a potential role of the dynamical feedback from Cl-VSLS-induced chemical ozone loss. Finally, we calculate the ozone depletion potential of dichloromethane, the most abundant Cl-VSLS, at 0.0107. Our results illustrate a so-far modest but nonetheless non-negligible role of Cl-VSLS in contributing to the stratospheric ozone budget over the recent past that if continues could offset some of the gains achieved by the Montreal Protocol.